Dispersi Kekuasaan sebagai Penghalang Otokratisasi: Paradoks Demokrasi Indonesia yang Terkompromikan - Muhammad Mutawalli Mukhlis; Muhammad Saleh Tajuddin; Wiranti Wiranti (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2025)
This article examines the persistence of Indonesia’s democratic system as a constitutional state (negara hukum), where popular sovereignty operates within the limits of the 1945 Constitution (UUD 1945). Although recent tendencies, such as the expansion of executive authority, electoral narrowing, media consolidation, and suppression of dissent, have weakened democratic quality, these developments have occurred within Indonesia’s distinctive constitutional framework, which combines democratic principles with Pancasila-based constitutional supremacy rather than liberal-constitutional doctrines. . Using a qualitative approach with descriptive-comparative analysis, this study draws on primary sources such as government policy documents and secondary materials, including academic journals and books, covering developments from 1999 to 2024. The analysis highlights two primary factors limiting autocratization: the redefinition of power distribution through the mechanisms of checks and balances and decentralization following the post-1998 constitutional reforms, and the continuous elite competition that prevents monopolization. Indonesian elites, while undermining democratic institutions to protect their privileges, remain committed to limited democracy as a framework for regulating elite rivalries. The constitutional design with term limits, separation of powers, and decentralization creates structural barriers against executive dominance. Furthermore, elite self-interest in maintaining political competition outweighs incentives for autocratic consolidation. Although civil society and public opinion contribute to resistance against backsliding, elite calculations are decisive. Thus, Indonesia’s experience demonstrates that elite-driven democracies can endure gradual democratic decline without collapsing into authoritarianism, provided that competition remains institutionally guaranteed and power remains dispersed. This dynamic ensures a stable yet compromised democratic system, shaped more by pragmatic elite interests than by normative democratic commitments.